Uso de estrategias co-curriculares para asegurar el aprendizaje de Química en estudiantes en riesgo académico en ingeniería (2025)
Assurance of Learning is a process focused on demonstrating the quality and effectiveness of education and learning. It involves the implementation of practices, policies, and procedures aimed at ensuring the development of skills, competencies, and knowledge expected to achieve within an educational program or learning environment. A problem of low academic performance has been identified in the subjects of Chemistry and General Chemistry I at La Sabana University, resulting in increasing rates of course repetition, student demotivation, and dropout. The research adopted a mixed-methods approach with a nested quasi-experimental design, applying differentiated strategies such as a leveling course, a gamified unit conversion kit, and an escape room game.